HUBUNGAN STATUS SOSIAL EKONOMI ORANG TUA DENGAN MOTIVASI BELAJAR SISWA (Studi Pada Siswa Kelas IV, V Dan VI di SDN 002 KINALI Kecamatan Kunatan Mudik) - Ayu Permata Sari; A. Mualif; Ikrima Mailani (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2023)
The purpose of this study was to determine the relationship between the socio-economic status of parents with the learning motivation of grade IV, V, and VI students in the subjects of Islamic Religious Education and Character Education at SDN 02 Kinali, Kuantan Mudik District, Kuantan Singingi Regency. In this study there are two variables studied.The population in this study are students in grades IV, V, and VI SDN 002 Kinali with a total of 37 students in the 2021/2022 academic year and the sample is 37 students. Data collection techniques were carried out by unstructured interviews, closed questionnaires and school documentation.This study consisted of two variables, namely the variable x (parents' socioeconomic status) and the variable y (student learning motivation). The data correlation analysis method used in this research is product moment correlation. Based on the results of data analysis, when compared to rcount with rtable at a significant level of 5%, it can be seen that rcount is 0.439 and rtable is 0.325, which means rcount is greater than rtable so Ha is accepted, Ho is rejected. Meanwhile, when compared to rcount with r table at 1% level, it can be seen that rcount is 0.439 and rtable is 0.418, which means rcount is greater than r table so Ha is accepted, Ho is rejected. So it can be concluded that there is a relationship between the socioeconomic status of parents and the learning motivation of students in grades IV, V, and VI in PAI and Budi Pekerti subjects at SDN 002 Kinali.